The Intersection of Service and Sales: The Increased Importance of Ambidexterity. (February 2020) - Rapp, Adam; Baker, Thomas L.; Hartmann, Nathaniel N.; Ahearne, Michael
Blurring roles in the front line are changing how many organizations interact with their customers. Whereas frontline employees were tasked with functional roles of service or selling, an increased competitive environment and growing customer expectations have caused a shift requiring many employees to be effective at both selling and service. The growth of sales/service ambidexterity in both practice and research has prompted more meaningful investigation of the topic. The purpose of this article is to provide a brief background of ambidexterity and positioning of the topic. We provide a discussion of the articles compiled in this special issue and the synergy across papers. We conclude with the implications of this research and avenues for future research.